Supercontinuum comb generated by soliton molecule pulse laser injecting into a nonlinear amplifying loop mirror. (June 2022) - Zhou, Renlai; Chen, Shijie; Li, Qian; Fu, H.Y.; Nakkeeran, K.
Highlights: Very first time, we experimentally demonstrated the generation of supercontinuum (SC) comb by pumping a tunable soliton molecule fiber laser output signal into a nonlinear amplifying loop mirror (NALM).We first experimentally demonstrated SC combs generation by pumping tunable soliton molecule pulses into a fiber NALM. SC signals with different comb-teeth structures were obtained by controlling the pump power and waveplate orientation of the polarization-maintained soliton molecule fiber laser. SC combs with different comb-teeth structures were obtained by controlling the pump power and waveplate orientation. Numerical simulations were carried out to elucidate the dual SC combs formation in the NALM, and to evaluate the degree of first-order coherence of the generated SC comb. Numerical simulations were carried out to elucidate the SC combs formation, and to evaluate the first-order coherence. Abstract: Very first time, we experimentally demonstrated the generation of supercontinuum (SC) comb by pumping a tunable soliton molecule fiber laser output signal into a nonlinear amplifying loop mirror (NALM). SC signals with different comb-teeth structures were obtained by controlling the pump power and waveplate orientation of the polarization-maintained soliton molecule fiber laser. The maximum achieved output powers of dual SC combs from two ports were 21.95 (output 1) and 3.75 mW (output 2), respectively. The spectral and temporal profiles of the SC comb were compared with the simulation results and the first-order coherence was evaluated. Our experiment provides a novel technique for the generation of SC signal with various comb-teeth structures that can be utilized in broadband spectrometers and full-field 3D metrology.